Visible Logic: Algorithmic Drawing and the Construction of Form (diségno, 2026)
The paper explores algorithmic drawing as both a critical and operational tool, highlighting its capacity to transform representation into a constructive process. Drawing has always possessed a generative nature: it does not merely depict an idea but establishes its validity by gradually constructing the spatial field of form. The digital transcription of algorithmic logics amplifies this dimension, translating the graphic gesture into sequences of rules, constraints, and parameters that render the entire design chain, from conception to realization, transparent. Indirect modeling, in particular, allows form to be conceived as a relational field, where dependencies among elements define coherent behaviors under transformation. The chain of models (conceptual, exploratory, continuous, procedural, fabrication, and physical) produces not only representations but genuine constructive programs capable of integrating geometric constraints, production requirements, and performance objectives. The case studies demonstrate how algorithmic drawing enables the management of complex forms, their translation into efficient constructive systems, and the preservation of project identity through variations, a visible logic that reaffirms and enhances the constructive nature of drawing.
Keywords: algorithmic drawing; indirect modeling; generative process; constructive logic